Tinjauan Ekonomi Islam Terhadap Gaya Hidup Remaja Anggota Arisan Online Di Desa Ngrupit - Anisa Ayu Ning Tyas; Ajeng Wahyuni (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
This study was conducted to determine the lifestyle of online arisan participants, influencing factors and lifestyle changes of online arisan participants. This research is a type of qualitative research. This study used primary data obtained directly from online arisan admins and online arisan members in Ngrupit Village. Data was collected through observation, interviews, and documentation. In the lifestyle of teenagers, members of online social gatherings include components of opinions, activities, and interests. Where teenagers like to live a hedonistic lifestyle so that it is not in accordance with the basic principles of consumption in Islam which likes simplicity, good example and is more concerned with needs than wants. The results showed that internal factors that influence the lifestyle of adolescents are different attitudes and personalities of each individual who wants to have a different lifestyle from other groups. In online gatherings, the cause of changes in the lifestyle of members is caused by those who have money and desire to follow the lifestyle of their friends. So that makes online social gathering a place to raise money so that what they want is fulfilled.